The Impact of Teachers’ Perspectives on Soft Skills Development A Study Based on 1Ab Super & 1Ab Schools At Jaffna Zone. - Srisundararajah, S.; Sathiaseelan, A. (Jaffna University International Research Conference, 2014)
This paper studies the impact of teachers’ perspectives on soft skills development at schools and the study based on the teachers of 1AB super & 1AB schools at Jaffna Zone. The data for the study have been collected from the 40% of teachers of 1AB super &1AB schools. This study attempts to find out that teachers’ perspectives impact on soft skills development at schools. The study sample consists of 46 teachers. Teachers’ perspectives are independent variables and soft skills development is dependent variable. The descriptive statistics was used to analyse the data and then Pearson’s correlation coefficient was used to identify the relationship between the variables. The impact of teachers’ perspectives on soft skills development was identified by using regression analysis. The study found that teachers’ knowledge on communicative skills & team work skills had strong positive correlation with soft skills development .Whereas awareness about soft skills had weak positive correlation. The findings also confirm that teachers’ knowledge on communicative skills & team work skills had significant impact on communicative skills & team work skills development. However, awareness about soft skills had no significant impact on communicative skills & team work skills development.
Keywords: Communicative skill